COMPARISON ANALYSIS OF PILE FOUNDATION CAPACITY SINGLE BASED ON PILE LOADING WITH PDA TEST ON SHAKING PORT DEVELOPMENT PROJECTCONTAINERS (APRON SLAB ON PILE) JAYAPURA - Duha Awaluddin Kurniatullah (Jurnal Education and Development, 2021)
The foundation is the main structure in a construction which functions as a support for the load or transmits the forces that occur above the construction and is transmitted into the hard soil. Pile foundations are part of the type of deep foundation that is widely used. In designing deep foundations using piles, there are several analytical methods to determine the bearing capacity of deep foundations.The purpose of this study is to calculate and compare the axial bearing capacity of single piles from the Meyerhoff SPT method data, the calendaring data from the Hiley method, ENR, WIKA, Eytelwein Chellis, Navy-Mc, Kay, Gates, Danish, and MSHoC, against the results of the test. PDA test axial bearing capacity. As for the calculation of the lateral bearing capacity using the Broms method.There is a difference in the value of the calculation results of bearing capacity and foundation settlement, both in terms of the calculation method and its location. Based on the calculation results of single pile axial bearing capacity with SPT data = 285,520 tons, calendaring data, Hiley = 336,994 tons, ENR = 50,156 tons, WIKA = 336,994 tons, Eytelwein Chellis = 88,718 tons, Navy-Mc, Kay = 5302,720 tons, Gates = 2802.460 tons, Danish = 9968.484 tons, MSHoC = 62.695 tons, while the results of the single pile axial bearing capacity using the PDA test obtained the results of = 392,000 tons. As for the calculation of the lateral bearing capacity of a single pile using the Broms method for the criteria for the pinned end pile foundation to be considered a long pile or not rigid, and the results obtained that the ultimate lateral force that can be resisted by the long wedged end pile is = 114.463 kg, and for The lateral allowable that can be resisted by the long pinned pile is = 38,154 kg, while the amount of deflection that occurs due to the allowable lateral force on the long wedged end pile foundation is 0.00549 mm. Differences in axial bearing capacity can be caused by differences in soil types, the way the test is carried out which depends on the accuracy of the operator and differences in the parameters used in the calculations.